The intensity and impact of drought on crop production and possibilities of mitigation in Serbia - Dragovic S.; Cicmil M.; Radonjic L.; Radojevic V. (Drought management: scientific and technological innovations, 2008)
Drought occurrence and intensity under agro-climatic conditions of Serbia cause considerable damage to agricultural production. The climatic conditions of Serbia are characterized by non-uniform rainfall, have changeable and unstable rainfall and dry periods between June and August. In July and August, drought occurrence is about 80% of years. Depending on drought intensity, crop yields could be reduced to 50% in relation to the genetic yield potential. In extremely dry years, yield reductions reach 90% in comparison with years with normal rainfall. Attention of drought mitigation includes various measures such as irrigation, genetics and breeding, agricultural practices, and others. Drought occurs occasionally in a single year or in a series of years, causing severe damage to agricultural production. In some years (e.g. 1951, 1990, 1992, 2000, 2003) drought was harmful not only to some crops but it affected the whole Pannonian Plain, or major parts of it, turning it into an arid region.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)